Assessment of Pesticide Degradation Efficacy of Probiotics Isolated From Foods - Vishalakshi Soundararajan; Preethu AH; Sonia Nayak S; Hanumantha Raju; Manikchandra Patil; Chennappa Gurikar (The Bioscan, 2025)
The extensive use of pesticides in agriculture has resulted in the presence of pesticide residues in food and feed, which poses a serious risk to human health. Many physical and chemical methods can be used to eradicate pesticides, but most of them are either costly or vulnerable to secondary contamination. Thus, the use of microorganisms, such as probiotics, to eliminate pesticides has emerged as a promising alternative. Some probiotic bacteria, mainly Lactobacilli, have received a lot of attention due to their toxicity reduction ability of several contaminants. For example, Lactobacilli can reduce the accumulation and toxicity of selective heavy metals and pesticides in animal tissues by inhibiting the intestinal absorption of contaminants and improving the intestinal barrier. Probiotics reduce the risk of antibiotic-associated diarrhea, perhaps by competing and producing antagonistic compounds against pathogenic bacteria. Mechanisms of these beneficial bacterial strains in the remediation process have been explored and especially their interaction with the host gut microbiota. In this review, we summarize research progress on the remediation mechanisms of some probiotics as well as the combined effects of probiotics and gut mirobiota on the remediation of foodborne contaminants in vivo.